Investigation of a laboratory technique for measuring fractional exhaled nitric oxide immediately after eating and drinking - NAKASHIMA, Kanako; NAGASHIMA, Koji; TOYOSAKI, Mitsuyo; NISHIO, Miho; HATAJI, Osamu; NISHIMURA, Haruka; USHIRO, Kengo; YAMAMOTO, Mako (Japanese Journal of Medical Technology, 2019)
Fractional exhaled nitric oxide (FeNO) is recognized as a marker of acidophilic inflammation in the lower respiratory tract. We can measure FeNO simply and noninvasively. On the other hand, it is reported that the FeNO level is affected when we consume a meal that includes nitric oxide, caffeine, and water. Also, there is very little information about the FeNO level immediately after eating and drinking. We examined the FeNO level immediately after consuming a meal and drink that include nitric oxide and caffeine, and determined the variation of water temperature. After consuming a meal that includes nitric oxide, we found significant decreases in the FeNO level after a minimum of 5 min. We did not find a significant difference after 30 min. The FeNO level significantly increased to the maximum after 1 h. After 2 h, it was high, which did not decrease to the level before the intake. After taking a drink that includes nitric oxide or caffeine, the level became the same as that after consuming a meal with nitric oxide. In the case of water temperature, the FeNO level significantly decreased 5 and 15 min after the intake of 4°C water. However, we did not find a significant difference in the FeNO level after the intake of 37°C water. We suggest that we should avoid FeNO measurement immediately after eating and drinking, and that the level is affected by the temperature of the drink. We consider that various factors are related to FeNO measurement conditions. Moreover, we believe that it is necessary to continue the examination of conditions affecting FeNO measurement in the future.